Changes in Posttraumatic Stress Disorder Symptoms after Participation in a Guided Internet-Based Trauma-Focused CBT Intervention: Results from a Pilot Study - Geležėlytė, Odeta; Guogaitė, Greta; Nomeikaitė, Augustė; Bisson , Jonathan; Lewis, Catrin; Jackūnaitė , Greta; Kasperavičiūtė , Emilija; Kazlauskas, Evaldas (Psichologija, 2025)
Posttraumatic stress disorder (PTSD) is a common mental disorder. However, only a part of people with PTSD receive the necessary treatment. Digital interventions could provide a more accessible alternative to the traditional face-to-face therapies. ‘Spring’ is an internet-based guided self-help intervention developed at Cardiff University (UK). It is based on the principles of trauma-focused cognitive behavioural therapy and has been developed with the objective to reduce mild to moderate PTSD symptoms associated with a single traumatic experience. The aim of this pilot study was to assess changes in the mental health indicators of individuals with PTSD after using the Lithuanian version of ‘Spring’. Data from seven women with PTSD who used the ‘Spring’ intervention were analysed. The mean age of the participants was 41 years (SD = 15). The results showed a significant reduction in posttraumatic stress, depression and anxiety symptoms, and an increase in psychological well-being after the intervention. The reduction in PTSD symptoms was statistically reliable for all participants, and six of the seven participants showed changes corresponding with a loss of their probable PTSD diagnosis after undergoing ‘Spring’. Overall satisfaction with the intervention was high. The early results from this pilot study of the Lithuanian version of ‘Spring’ guided internet-based intervention show that it can be a promising PTSD treatment method. More research is still needed to evaluate the efficaciousness of ‘Spring’ in larger samples.
Keywords: posttraumatic stress disorder; PTSD; internet-based intervention; cognitive behavioural therapy